The Implementation of Reading Interest Literacy in the Merdeka Curriculum in Indonesian Language Learning in Grade III at SD Negeri 19 Kampung Baru, Pesisir Selatan Regency - Mesy Putri Yusda; Nofriza Efendi; Gusnita Efrina; Yona Syaida Oktira (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to describethe implementation of student’s reading interest literacy within the merdeka curriculum during indonesian language learning in the third grade at SD Negeri 19 Kampung Baru, Pesisir Selatan. This research employs a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation. Subseqently, data analysis, was conducted in three stages: data reduction, data presentation, and conclusion drawing. The research subjects were the third – grade homeroom teacher and third – grade studentss. The results of data analysis, which involvet collecting information from different informants and analyzing finding in the field, indicate that the implemantation of reading interest literacy in the third grade at SD Negeri 19 Kampung Baru is conducted through a program of 15 minutes of reading activity before lessons begin. The supportinh factors for studdents’ reading interest literacy imclude enjoyment of reading materials and the increase of students’ reading interest. Meanwhile, the inhibiting factors consist of the influence of mobile phones and limited supporting facilities.